Developing A Method for Estimation of Tightness Based on Calibration Characteristics - Asadova, Yu.S.; Nemenko, M.V.; Volodina, A.M. (International Journal of Engineering and Technology, 2018)
This article discusses methods of assessing tightness of mass-produced products. In order to reduce errors in the calibration of gas analytical leak detectors, a method is proposed which is based on transferring a certain number of molecules from the measuring chamber. This is done by means of a throttle device called frequency resistance. Based on the tests performed, results of the study are displayed.